Antibiotic resistance in foodborne bacteria. (February 2019) - Caniça, Manuela; Manageiro, Vera; Abriouel, Hikmate; Moran-Gilad, Jacob; Franz, Charles M.A.P.
Abstract: Background: Antibiotic resistance, mainly due to imprudent use of antibiotics in agriculture, environment, animal and human medicine, has been widely recognized as one of the main global health concerns, threatening food security, and human and animal health, causing considerable economic losses. Scope and approach: We summarize the state of the art in antibiotic resistant foodborne bacteria and related reservoirs, some actions to overcome this threat, and the future perspectives in the field. Key findings and conclusions: Food and food production may be a vehicle of antibiotic resistant bacteria and antibiotic resistance genes to humans that have a public health impact. Mobile genetic elements such as plasmids, transposons, have the ability to form hybrid elements interplaying with or from the environment and foodborne bacteria. These genetic structures are able to encode for resistance for many antibiotics, namely those that are last resort treatments for patients infected with multidrug resistant bacteria. Information, education and training, surveillance, monitoring, record-keeping, reduction of infection, legislation, optimization and reduced antibiotic use, and sustainable investment for alternatives, are important actions to bring antibiotic resistant foodborne bacteria under control. Omics technologies such as genomics, metagenomics and transcriptomics, are valuable tools for surveillance and control of antibiotic resistance in different One Health settings, notably with respect to the selection, dissemination, and distribution of antibiotic resistant bacteria in food, as well as to unravel the antibiotic resistance mechanism involved. In the future metatranscriptomics, proteomics and metabolomics are expected to enlarge next-generation-sequencing tools to strengthen control of antibiotic resistance in food. Highlights: Alarming trends of antibiotic resistance. Spread of antibiotic resistance via food chain animals, foodstuffs and water. Taking action to fight against antibiotic resistance in food. New tools to underpin control of antibiotic resistance in food.